Phase control of sputter-grown large-area MoTe2 films by preferential sublimation of Te: amorphous, 1T ' and 2H phases - Hatayama, Shogo; Saito, Yuta; Makino, Kotaro; Uchida, Noriyuki; Shuang, Yi; Mori, Shunsuke; Sutou, Yuji; Krbal, Miloš; Fons, Paul (Royal Society of Chemistry, 2022)
Sputter-grown amorphous Mo-Te films were annealed to obtain the crystalline phase. Although as-deposited films exhibited an off-stoichiometric Te-rich composition, optimized annealing conditions enabled the elimination of excess Te by a preferential sublimation process. Owing to their similar local structure, the disordered amorphous phase first crystallized into a high temperature phase, 1T ', followed by a phase transition to the 2H structure upon further annealing. To realize 2D MoTe2-based novel devices, understanding the crystallization mechanism of amorphous Mo-Te films is critical. Furthermore, the robustness of the fabrication method, i.e., the establishment of a method to realize MoTe2 single-phase formation, which does not require the initial composition of the as-deposited amorphous film to be exactly stoichiometric, will greatly contribute to the deposition of large-area MoTe2 films essential for industrial applications.
Fázové řízení naprašovaných filmů MoTe2 na velkou plochu preferenční sublimací Te: amorfní, 1T´ a 2H fáze
Keywords: MoTe2; crystallization; optimized annealing conditions; sublimation; structure; MoTe2; krystalizace; optimální podmínky žíhání; sublimace; struktura